Resultados de saúde das mulheres atendidas nas consultas de enfermagem para a prevenção do câncer de colo do útero - Gomes, Maria Luziene de Sousa (2020)
Cross-sectional, retrospective and descriptive study that analyzed the health results of women attended in nursing consultations for the prevention of cervical cancer in a health-school unit linked to the Federal University of Ceará (UFC). The gynecological nursing consultations followed the precepts of the PROGYNE protocol, including physical examination, clinical breast examination, cytopathology, digital cervicography (DC) and colposcopy, and were carried out from March to July 2016 involving a sample of 87 women. Pearson's chi-square test was used, considering p <0.05 and the strength of this association by calculating odds ratios (Odds Ratio - OR). Examination accuracy was measured by sensitivity, specificity, diagnostic odds ratio (DOR), diagnostic accuracy, positive predictive value (PPV), negative predictive value (NPV) and likelihood ratio (LR) for positive test (likelyhood ratio), with colposcopy as the gold standard. The research was approved by the ethics committee (No. 401.240). The analysis indicated a predominance of young women (M = 32.9 ± 10 years), brown (67; 77%), married (62; 71.3%), with up to nine years of schooling (45; 51.7%) and housewives (46; 52.9%); heterosexuals (80; 92%), with sexarche between 16 and 20 years old (40; 46%), with up to five partners (74; 85.1%). Regarding clinical examinations, eight (9.2%) had the Schiller + test; colposcopy 13 (14.9%) were irregular, 66 (75.9%) normal and eight (9.2%) unsatisfactory; DC + in 45 (51.7%) women. Regarding the cytopathological report, 76 (87.4%) were normal. The abnormal results were: ASC-US (4, 4.6%), ASC-H (3, 3.4%), LSIL (2, 2.3%) and HSIL (2, 2.3%). In the history of sexual health, the variables sexually transmitted infection (STI) history (p = 0.025 [OR95% = 7.22 (1.86 - 60.49)]) and use of oral contraceptives (p = 0.035 [OR95% = 3.78 ( 0.98 - 14.55)]) were significant for the annual preventive exam and the self-reported color black (p = 0.031 [OR95% = 15.60 (1.80 - 135.06)]) showed a significant association for the first gynecological consultation. Having undergone the first cytopathological examination within the first three years of sexual initiation was associated with a single marital status (p = 0.031), as well as having a family history of cancer (p <0.001). The positive result of colposcopy was associated with age up to 30 years (p = 0.027 [OR95% = 0.25 (0.07 - 0.90)]) and being single (p = 0.021 [OR95% = 0.23 (0.07 - 0.80)]). The cytopathological exam was the one with the best accuracy and the highest diagnostic odds ratio. However, implementing colposcopy in primary care is relevant to assist in the screening, diagnosis and timely treatment of precursor lesions and the consequent reduction in cases of cervical cancer, since it is an accurate procedure considered to be the gold standard. Understanding the health outcomes of women who attended the cervical cancer prevention consultation, as well as the screening methods used, is essential to the service and national health system of less developed countries, such as Brazil.